A Practical Procedure for Regioselective Bromination of Anilines - Takahashi, Yusuke; Seki, Masahiko (Synthesis, 2021)
A highly practical procedure for the preparation of bromoanilines by using copper-catalyzed oxidative bromination has been developed. Treatment of free anilines with readily available NaBr and Na2S2O8 in the presence of a catalytic amount of CuSO4·5H2O enabled regioselective bromination.
Keywords: anilines; bromination; catalysis; copper; halides; halogenation; oxidation